(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Neonatal jaundice is a relatively common phenomenon, which is frequently associated with the condition of the newborn, having hemolysis from the incompatibility of maternal antibodies with the fetal red blood cells, and ABO blood groups. Such incompatibility is especially prevalent in areas with high rates of consanguinity including Pakistan. It is imperative to know its prevalence in jaundiced neonates to facilitate early diagnosis and management, which in turn will minimize complications and improve neonatal outcome in resource-constrained settings. METHODOLOGY: This prospective descriptive study was conducted at Ghulam Muhammad Ali Mahar Medical College Teaching Hospital and 174 full-term (0–28 days) neonates were included in the study by non-probability consecutive sampling. ABO incompatibility was assessed through comparison of maternal and neonatal blood groups in neonates diagnosed with jaundice (bilirubin >15 mg/dL). Data were analyzed using SPSS 26.0 RESULTS: ABO incompatibility was found in 16.3% of jaundiced neonates, with 49% males and 51% females, and a mean age of 13.3 ± 8 days. It was significantly associated with anemia (22.4%, OR 6.8), elevated bilirubin levels (>22 µmol/L, OR 0.26), positive Coombs tests (24.1%, OR 2.5), hemolysis (31.4%, OR 3.5) and IVIG therapy was found to be in (28.6%, OR 3.1) cases. CONCLUSION: It is to be concluded that ABO incompatibility is an important cause of jaundice in a neonate with a higher risk of anemia, hemolysis, and hyperbilirubinemia requiring an intensive therapy line, such as IVIG therapy. Within this already vulnerable subgroup of patients, early detection and treatment, such as with phototherapy and occasionally also exchange transfusions, is crucial for minimising sequelae and for improving neonatal outcome.